Untargeted analysis in post-COVID-19 patients reveals dysregulated lipid pathways two years after recovery - López-Hernández, Yamilé; Oropeza-Valdez, Juan José; García Lopez, David Alejandro; Borrego, Juan Carlos; Murgu, Michel; Valdez, Jorge; López, Jesús Adrián; Monárrez-Espino, Joel (Frontiers in Molecular Biosciences, 2023)
Similar to what it has been reported with preceding viral epidemies (such as MERS, SARS, or influenza), SARS-CoV-2 infection is also affecting the human immunometabolism with long-term consequences. Even with underreporting, an accumulated of almost 650 million people have been infected and 620 million recovered since the start of the pandemic; therefore, the impact of these long-term consequences in the world population could be remarkable. It took a while, but finally, the World Health Organization recognized the post-COVID syndrome as a new entity, and guidelines are being established to manage and treat this new condition. However, there is still uncertainty about the molecular mechanisms behind the large number of symptoms reported worldwide. In this study we aimed to evaluate the clinical and lipidomic profiles (using non-targeted lipidomics) of recovered patients who had mild and severe COVID-19 infection (acute phase, first epidemic wave); the assessment was made two years after the initial infection. Results show fatigue (59%) and musculoskeletal disorders (50%) symptoms as the most relevant and persistent. Functional analyses revealed that sterols, bile acids, isoprenoids, and fatty esters were the predicted metabolic pathways affected in both COVID-19 and post-COVID-19 patients. Principal Component Analysis showed differences between the study groups. Several species of phosphatidylcholines and sphingomyelins were identified and expressed in higher levels in post-COVID-19 patients with respect to controls. The paired analysis (comparing patients with an active infection and two years after recovery) show 170 dysregulated features. The relationship of such metabolic dysregulations with the clinical symptoms point to the importance of developing diagnostic and therapeutic based on cell signaling pathways.